1996
DOI: 10.1046/j.1365-2141.1996.5151055.x
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor enhances survival and cytotoxic activity of human eosinophils

Abstract: Phenotypic change of blood-type eosinophils to tissue-type eosinophils is induced by various cytokines. We examined the effect of nerve growth factor (NGF) as a candidate for a constitutive cytokine which is able to induce the phenotypic change of eosinophils. The viability of human peripheral blood eosinophils cultured for 4 d was increased from a mean of 26% to a mean of 50% (P<0.001) by the addition of NGF (50 ng/ml). Cytotoxic activity of eosinophils determined by larvicidal activity was increased 2-3-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 16 publications
1
48
1
Order By: Relevance
“…NGF has been demonstrated as an important factor for hematopoietic colony growth and differentiation [41]. Previous work documents its ability to directly influence proliferation, differentiation, and maturation of myeloid progenitors along with induction of migration, survival and activation of mature hematopoietic cells [42][43][44]. NGF is also a chemotactic stimulus for human leukocytes and macrophages [45,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NGF has been demonstrated as an important factor for hematopoietic colony growth and differentiation [41]. Previous work documents its ability to directly influence proliferation, differentiation, and maturation of myeloid progenitors along with induction of migration, survival and activation of mature hematopoietic cells [42][43][44]. NGF is also a chemotactic stimulus for human leukocytes and macrophages [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…As such, neurotrophins are positioned to regulate the availability of inflammatory cells derived from the marrow, through both direct [41][42][43][44] and indirect mechanisms. Taken together, our data suggest a central role for neurotrophins in the inflammatory process subsequent to infection and identify bone marrow stroma as a novel target for these factors.…”
Section: Discussionmentioning
confidence: 99%
“…The study results suggest that anti-NGF antibodies block the effects of NGF on the periphery of the nervous system and suppress epidermal innervation, dermatitis, and scratching behavior. There is also growing evidence that NGF has biological effects on immune cells, such as mast cells (34), B cells (35), T cells (36), neutrophils (37), eosinophils (38), and basophils (39). Anti-NGF antibodies may suppress these symptoms in NC / Nga mice by blocking response to these immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…In prior studies, we have demonstrated that NGF promotes not only granulocyte differentiation from human PBMC and murine bone marrow cells (12,13), but also differentiation of connective tissue-type mast cells from murine bone marrow cells and bone marrow-derived culture mast cells (14). NGF is capable of supporting survival of neutrophils (15), eosinophils (16), and mast cells (9) by preventing apoptosis, and enhancing functional properties of neutrophils, eosinophils, macrophages, and mast cells: phagocytosis, superoxide production, matrix metalloproteinase-9 production, and chemotaxis (11, 12, 16 -20). These experimental findings strongly support a possibility that NGF acts as a cytokine that is capable of modulating inflammatory responses and tissue repair.…”
Section: N Erve Growth Factor (Ngf)mentioning
confidence: 99%